Mapeamento das evidências da colaboração Cochrane para condutas em saúde - El Dib, Regina Paolucci [UNIFESP] (2006)
Context: we consider systematic reviews the best level of evidence for the decision making in the health care, which methodological severity offers a diversity of implications to clinical practice and to scientific research. Objective: to assess the proportion of the complete systematic reviews of Cochrane Colaboration that allow practice application of results and implication to scientific research. Design and Setting: Cross-sectional study of systematic reviews of Cochrane Library issue 4, 2004. Main Outcomes Measures: 1016 systematic reviews published throughout 50 Cochrane Collaborative Review Groups were analysed randomly. Data extraction was based on the authors’ conclusions, meta-analysis interpretations and on the context of each systematic review. The implications to practice had been classified in three categories: A) evidences that support the use of the tested intervention. B) evidences that contraindicate the intervention use. C) absence of evidences to recommend or discourage the intervention. The implications to scientific research had been categorized in: 1) recommendation to further research and 2) no necessity to recommend new studies. Number of included studies and meta-analysis were also quantified. Results: 1016 systematic reviews were analyzed, which corresponded to 46,60% of the available totality in the Cochrane Library, issue 4, 2004. The proportions and confidence interval (CI) of 95% of the implications to clinical practice were: A) 44,39 (95% IC, 42,16 – 46,62) %; B) 6,79 (95% IC, 5,66 – 7,92)%; C) 48,81 (95% IC, 46,57 – 51,07)%. The totality of systematic reviews that recommend the accomplishment of further studies was 13.830 (medium 8 and mode 2) and the totality of included meta-analysis of the evaluated systematic reviews, 6.641 (medium 2 and mode 0). Conclusion: the great majority of systematic reviews do not bring specific orientations with relations to the benefit or curse of an intervention, comparatively to control group for certain clinical situation. There are a significant proportion of systematic reviews that suggest recommendations of new studies to answer to the clinical question of the review. There are few primary studies that answer the inclusion criterion of the systematic review and suggest a poor methodological quality. There is a little amount of meta-analysis by systematic review for the clinical outcomes of interest.